Effectiveness of online education about actions of 3G motions to maintain children's oral health in the new normality era of the COVD-19 Pandemic - Reno Wiska WULANDARI; Didin KUSTANTININGTYASTUTI; Suci RAHMASARI; Wulandani Liza PUTRI; Fildzah Nurul FAJRIN; Riska Ananda PRATIWI; Safira FAJRIATI (Journal of Syiah Kuala Dentistry Society, 2022)
The actions of 3G are three motions to maintain oral health: brushing teeth, using mouthwash, andchanging the toothbrush once in 3 months. People have to brush their teeth twice a day in the morning and nightbefore sleeping, using mouthwash, and evolving their toothbrush once in 3 months is the third movement of 3G.These actions can clean teeth from bacteria and viruses. This study aims at analyzing the effectiveness of onlineeducation about the actions of 3G to maintain oral health during the COVID-19 Pandemic. This research is a crosssectionalanalytical study with data collection using a questionnaire conducted online through an electronicquestionnaire form held on June 17, 2021. Respondents in this study were 52 fourth-grade SD Kartika 1-11 Padangstudents selected by purposive sampling technique. The research data were processed with SPSS statistical software.This study reveals education about 3 G increase the knowledge of children about the importance of brushing teeth,using mouthwash, and changing toothbrush once in 3 months, besides the low effectiveness of online educationabout 3 G. This study concludes that online education was not effective to increase respondent's knowledge aboutactions of 3 G to maintain oral health during the Covid 19 pandemic.KEYWORDS: Oral health education, toothbrush, mouthwash, 3G, COVID-19 virus